Development of Registry Data to Create Interactive Doctor-Patient Platforms for Personalized Patient Care, Taking the Example of the DESTINY System - Bergmann, Arnfin; Stangel, Martin; Weih, Markus; van Hövell, Philip; Braune, Stefan; Köchling, Monika; Roßnagel, Fabian (Frontiers in Digital Health, 2021)
‘Real-world evidence (RWE)’ is becoming increasingly important, to integrate the results of randomized studies into day-to-day clinical practice. Almost all the data collected to date come from evaluations of large-scale national and international registries. NeuroTransData (NTD), a network of neurologists and psychiatrists throughout Germany, has developed these registry data further to create a digitalized doctor-patient platform known as DESTINY (DatabasE-assiSted Therapy decIsioN support sYstem). This platform can be integrated into day-to-day practice and, as well as being used for scientific evaluations in healthcare research, can also serve as an individual, personalized treatment application. Its various modules mean that it can quickly identify side-effects and interactions of a treatment, can involve patients via the ‘My NTC Health Guide’ portal and, by the use of innovative algorithms, can collect predictive data (currently for multiple sclerosis – other indications are in the pipeline) taking account of individual clinical histories. Such systems offer the potential for improved personalized healthcare.